Structure of the IscB–ωRNA ribonucleoprotein complex, the likely ancestor of CRISPR-Cas9 - Kazuki Kato; Sae Okazaki; Soumya Kannan; Han Altae-Tran; F. Esra Demircioglu; Yukari Isayama; Junichiro Ishikawa; Masahiro Fukuda; Rhiannon K. Macrae; Tomohiro Nishizawa; Kira S. Makarova; Eugene V. Koonin; et al. (Nature Communications, 2022)
The cryo-EM structure of the IscB–ωRNA–target DNA complex provide insights into the ωRNA-guided DNA cleavage mechanism by IscB and the evolution of the type II CRISPR-Cas9 effector complexes